Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

(9-3)+18÷9
show your work ​


Sagot :

(9-3)+18÷9

= 6+18÷9

= 6+2

= 8

Answer:

8

Step-by-step explanation:

Well, we need to use order of operations. Since there are parenthesis, we solve what is inside that first. So, 9-3=6. We have solved one part of the equation. There are no exponents so division comes next. 18/9=2. Now we are left with 6+2. 6+2=8. Therefore, your final answer is 8.